A virtual reality paradigm for the study of visually mediated behaviour and cognition in spiders. (September 2015) - Peckmezian, Tina; Taylor, Phillip W.
Abstract : Jumping spiders (Salticidae) are well known for their unique, high-acuity visual system and complex, visually mediated behaviour. To overcome the limitations of video playback and other open loop systems that are currently available for the study of visually mediated behaviour in jumping spiders, we developed a closed-loop, virtual reality (VR) system in which a spider on a spherical treadmill walks through a projected 3D world that updates in real time in response to its movements. To investigate VR as an experimental technique for spiders as well as validate it as a proxy of the real world, we conducted two experiments to assess whether individual behavioural tendencies and learning transferred from real to virtual environments. In the first experiment, we examined transference of individual behaviour tendencies (spontaneous locomotion and dark/light preference) between real and VR environments, and found that individual differences were conserved. In the second experiment, we investigated transference of beacon-learning tasks between real and VR environments. We found that spiders that had learned a beacon–nest site association in the real world tended to expresses similar associations in the virtual world. Virtual reality offers great promise as a new tool to explore the cognitive processes underlying vision-mediated learning, memory and navigation in jumping spiders. Highlights: We created an immersive virtual reality system for jumping spiders. Activity patterns in the virtual worlds mirror those in the real world. Spiders show similar light/dark preference in real and virtual environments. Spiders learn a beacon–nest site association in the real world. Real world experiences influence behaviour in virtual reality.